1985
DOI: 10.1021/bi00347a050
|View full text |Cite
|
Sign up to set email alerts
|

Implication of the "4S" polycyclic aromatic hydrocarbon binding protein in the transregulation of rat cytochrome P-450c expression

Abstract: A protein which specifically binds [3H]benzo[a]pyrene and other polycyclic aromatic hydrocarbons has been purified over 6000-fold from rat hepatic cytosol by using ion-exchange, gel permeation, and hydrophobic interaction chromatography. The binding protein differs from the 9S binding protein characterized in other laboratories. A Stokes radius of 2.75 nm was determined by gel filtration on Sephadex G-100. A sedimentation coefficient of 3.3 S was determined by using sucrose gradient analysis. The ability of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1988
1988
2003
2003

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…Previously, B[e]P had been demonstrated to be a selective ligand for the 4 S PAH-binding protein (17)(18)(19)(20)(21)(22)(23). In the present study, we have shown that this PAH is also able to induce the expression of CYP1A1 in the GNMT-transfected CHO cells, whereas TCDD, a prototypic ligand for the Ah receptor, failed to do so.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Previously, B[e]P had been demonstrated to be a selective ligand for the 4 S PAH-binding protein (17)(18)(19)(20)(21)(22)(23). In the present study, we have shown that this PAH is also able to induce the expression of CYP1A1 in the GNMT-transfected CHO cells, whereas TCDD, a prototypic ligand for the Ah receptor, failed to do so.…”
Section: Discussionsupporting
confidence: 47%
“…Evidence has been published suggesting that the induction of rat CYP1A1 after treatment with PAHs, such as B[a]P or B[e]P, may require an Ah receptor-independent pathway mediated by another cytosolic receptor protein, the 4 S PAHbinding protein (17)(18)(19)(20)(21)(22)(23). Both the Ah receptor and 4 S PAHbinding protein exhibit distinct ligand binding specificities, with 3-methylcholanthrene interacting with both.…”
mentioning
confidence: 99%
“…Recently, a benzo[a]pyrene-binding protein was purified from rat hepatic cytosol [6]; the complex was able to bind total rat liver DNA as well as subclones containing portions of the rat cytochrome P-450c gene, implicating this 4-S protein in the transregulation of its expression. The present report provides additional information on the binding capacities of the 4-S protein.…”
Section: Discussionmentioning
confidence: 99%
“…The differences in timecourse may be due to differences in the half-lives of the relevant mRNAs andor proteins (Hargrove and Schmidt, 1989), and it is clear that parallel dose-response curves for different biological responses can be separated by as much as several orders of magnitude and still be mediated by the same receptor (Okey et al, 1995). It is important to point out that a rat liver cytosolic 4 S carcinogen-binding protein may also be involved in the transcriptional induction of CYPl A I expression in response to nonhalogenated aromatic hydrocarbons (Houser et al, 1985 LeBlanc and Waxrnan, 1990) and cytokines and inflammatory mediators (Morgan, 1989;Morgan. 1993;Chen et al, 1995b) being the best characterized negative regulators.…”
Section: Correlation Analysismentioning
confidence: 99%